Racial and Ethnic Disparities in Referral to Outpatient Heart Failure Management at Hospital Discharge: A Get With The Guidelines Analysis - Maggie Wang; Xinwei He; Kaylyn Crawford; Yi‐An Ko; Neal W. Dickert; Shivani A. Patel; Ambarish Pandey; Ersilia M. DeFilippis; Khadijah Breathett; Rebecca Cogswell; Clyde W. Yancy; Gregg C. Fonarow; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Black and Hispanic patients with heart failure (HF) have a higher risk of adverse clinical outcomes. Currently, it is unclear whether there are disparities in referral to outpatient HF management programs based on race and ethnicity. Methods and Results We used the American Heart Association GWTG‐HF (Get With The Guidelines‐Heart Failure) registry to examine 402 225 patients hospitalized for acute HF from January 1, 2010 to December 31, 2021. Logistic regression was used to examine the association of race and ethnicity with the likelihood of referral to outpatient HF management programs, adjusted for demographics, hospital characteristics, distressed community index score, comorbidities, and indicators of HF severity. Of the 402 225 patients hospitalized for acute HF during the study period (mean age 72 years, 47% female, 44% with ejection fraction <40%), 220 354 (55%) patients were referred to an outpatient HF management program at hospital discharge. In fully adjusted models, patients who self‐identified as Hispanic (odds ratio [OR], 0.87 [95% CI, 0.84–0.90]), Asian (OR, 0.74 [95% CI, 0.70–0.78]), and other (American Indian, Alaska Native, Hawaiian Native, or Pacific Islander, OR, 0.85 [95% CI, 0.82–0.89]) had a lower likelihood of referral to outpatient HF management programs than White patients. There were no differences in referral likelihood between Black and White patients. Conclusions In the GWTG‐HF registry, patients from minoritized racial and ethnic groups, aside from Black patients, were less likely than White patients to be referred to outpatient HF management programs after HF hospitalization. Addressing these differences in referral practices may improve HF outcomes in minoritized communities.